Structure of the cohesin loader Scc2 - William C. H. Chao (Nature Portfolio, 2017)
The cohesin complex maintains genome integrity by ensuring correct sister-chromatid segregation during mitosis and meiosis. Here, Chaoet al. present a pseudo-atomic model of the full-length Scc2–Scc4 cohesin loader complex and reveal key Scc2 surfaces crucial for cohesin loading.